Alanine and proline content modulate global sensitivity to discrete perturbations in disordered proteins. Issue 12 (10th October 2014) - Perez, Romel B.; Tischer, Alexander; Auton, Matthew; Whitten, Steven T.
ABSTRACT Molecular transduction of biological signals is understood primarily in terms of the cooperative structural transitions of protein macromolecules, providing a mechanism through which discrete local structure perturbations affect global macromolecular properties. The recognition that proteins lacking tertiary stability, commonly referred to as intrinsically disordered proteins (IDPs), mediate key signaling pathways suggests that protein structures without cooperative intramolecular interactions may also have the ability to couple local and global structure changes. Presented here are results from experiments that measured and tested the ability of disordered proteins to couple local changes in structure to global changes in structure. Using the intrinsically disordered N‐terminal region of the p53 protein as an experimental model, a set of proline (PRO) and alanine (ALA) to glycine (GLY) substitution variants were designed to modulate backbone conformational propensities without introducing non‐native intramolecular interactions. The hydrodynamic radius (Rh) was used to monitor changes in global structure. Circular dichroism spectroscopy showed that the GLY substitutions decreased polyproline II (PPII) propensities relative to the wild type, as expected, and fluorescence methods indicated that substitution‐induced changes in Rh were not associated with folding. The experiments showed that changes in local PPII structure cause changes in Rh that are variable and that depend on the intrinsic chain propensities of PRO and ALA residues, demonstrating a mechanism for coupling local and global structure changes. Molecular simulations that model our results were used to extend the analysis to other proteins and illustrate the generality of the observed PRO and alanine effects on the structures of IDPs. Proteins 2014; 82:3373–3384. © 2014 Wiley Periodicals, Inc.